Incomplete by Design: Notes Around Late SoTL - Parker, Matthew (Imagining SoTL, 2026)
This article examines how assessment in SoTL is shaped not only by methodological rigour but also by the aesthetic forms through which knowledge becomes recognizable. Drawing on architectural theory, it introduces the concept of lateness to describe a condition in which established scholarly forms remain operative while revealing their own limits. Lateness names a moment of reflective mastery, when disciplinary practices become self-aware enough to see how their familiar patterns both sustain and constrain what can be recognized as learning.The paper argues that assessment is inseparable from questions of appearance, legibility, and recognition. Elements such as structure, pacing, citation, and presentation quietly shape evaluative judgments, often in advance of explicit criteria. Through a close reading of SoTL’s evaluative norms and a pedagogical case drawn from an experimental elective, the article shows how openness to multiple methods can solidify into narrow aesthetic expectations.Rather than proposing alternative metrics and assessment tools, the paper explores the conditions under which learning becomes visible and valued in the first place. By reframing assessment as an aesthetic and epistemological practice, lateness offers a way to remain attentive to forms of learning that do not resolve neatly, without converting indeterminacy into failure.